Policy Models on the Development of Intellectual Capital and Creative Economy to Strengthen Tourist Attractions in the Lower Northeastern Province, Thailand - Suthamdee , Dasarinpat; Chueasraku, Chinnawat (Journal of Politics and Governance, 2025)
Due to Thailand's abundant natural resources and rich cultural heritage, it presents a significant opportunity for further investigation into policy models aimed at enhancing intellectual capital and promoting the creative economy to elevate tourist attractions within the "Nakhon Chai Burin provincial group". The objectives of this study were twofold: firstly, to explore the relationship between intellectual capital and the creative economy in the enhancement of tourist attractions within the Nakhon Chai Burin provincial group, and secondly, to devise a policy model for the development of intellectual capital and the creative economy to uplift tourist destinations in this provincial group. This research employed qualitative methodologies, including documented research methods, in-depth interviews, and focus group discussions, to gather and analyze data. The findings were presented through analytical and synthetic means, with interpretative inductive conclusions drawn from the results. The research findings unveiled significant relationships between intellectual capital—encompassing human, relationship, and structural capital—and the creative economy, leading to the enhancement of tourist attractions within the Nakhon Chaiburin provincial group. Notably, a statistically significant positive correlation was observed between these variables and the upgrading of tourist destinations in the Nakhon Chaiburin provincial group. Various factors pertaining to the development of intellectual capital and the principles of the creative economy were identified as influential in the enhancement of tourist attractions within this region. These factors encompass human capital elements, relationship capital dynamics, structural capital components, and concepts intrinsic to the creative economy. Policy models designed to foster intellectual capital development and promote the creative economy for the advancement of tourist attractions in the Nakhon Chaiburin provincial group were delineated as follows: firstly, the promotion of human capital factors through initiatives aimed at nurturing talent, enhancing skills, fostering adaptability, bolstering communication proficiencies, cultivating interpersonal relationships, and nurturing effective leadership; secondly, the promotion of relationship capital factors, entailing activities such as public relations endeavors, promotional campaigns, and the establishment of local networks; thirdly, the encouragement of structural capital development, emphasizing the establishment of clear objectives, the cultivation of a culture of collaborative effort, and the enhancement of operational efficiency; fourthly, the advocacy for integrating the principles of the creative economy into operational frameworks, with an emphasis on fostering innovation and uniqueness. Consequently, it is imperative to prioritize the preservation and cultivation of elements related to intellectual capital and the creative economy to optimize the efficacy of upgrading tourist attractions within the Nakhon Chaiburin provincial group.